Whether Financial Inclusion Improves Employment Structure and Labor Allocation: Evidence From China’s Industrial Restructuring - Yiqing He; Yijin Pan; Xuhong Yuan (SAGE Open)
Enhancing the employment structure and alleviating the degree of labor-capital mismatch promotes domestic demand growth, economic restructuring, and long-term stability, resulting in high-quality economic development. In light of this, this paper investigates the impact and influence of inclusive finance on employment structure and labor mismatch. In response to an empirical study using data from 271 cities, the growth of inclusive finance has a considerable positive influence on both employment structure and labor factor mismatch. On this premise, the mechanism test discovers that industrial advanced adjustment, rationalization adjustment, and industrial adjustment intensity play diverse intermediary roles; The labor resource mismatch index can be lowered and the employment structure can be improved using industrial advanced adjustment, while the pursuit of the degree of industrial coordination is not always conducive to the realization of the effective allocation of the employment structure, and the intensity of industrial adjustment is too high, even though it significantly promotes the upgrading of the employment structure, it also exacerbates labor mismatch.. The heterogeneity test then reveals that the effects of inclusive finance on labor factor mismatch and employment structure varied depending on city size and geographic variations. JEL Classification: J21, L16, R51.